Growth Performance of Elephant Grass (Pennisetum purpureum) Treated with Liquid Organic Fertilizer from Cattle Urine and Fruit Waste - Maulina Novita; RAHMAT HIDAYAT; Dedi Ramdani; M. Zaki; Vebrita Sari (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study aims to determine the effect of liquid organic fertilizer (LOF) made from a mixture of cattle urine and fruit waste on plant height growth, leaf length, and fresh weight of elephant grass (Pennisetum purpureum). The study used a Completely Randomized Design (CRD) with 4 treatment levels and 5 replications, namely P0 (control / without LOF), P1 (50 ml LOF/liter of water), P2 (100 ml LOF/liter of water), and P3 (150 ml LOF/liter of water). The results showed that the application of cattle urine and fruit waste liquid organic fertilizer significantly affected plant height, leaf length, and fresh weight production of elephant grass. The treatment with the highest concentration, namely 150 ml LOF/liter of water (P3), yielded the best results for plant height growth (140.60 cm), leaf length (130.20 cm), and fresh weight of elephant grass (3,637.00 grams).